2019
DOI: 10.1002/mnfr.201900109
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in Rats Causes Cardiac Dysfunction by Inducing Myocardial Insulin Resistance

Abstract: Scope Cause‐effect relationship between vitamin D deficiency and cardiometabolic abnormalities remains undefined. The aim is to investigate the role of vitamin D deficiency in cardiac failure, through possible involvement in myocardial insulin signaling. Methods and results Male SD rats (n = 6) are fed a normal diet (Con), vitamin D‐deficient diet [Con(‐)], or high‐fat, high fructose diet (HFHFrD) for 20 weeks. Cardiac hypertrophy and fetal gene program are confirmed in Con(‐) group. Cardiac dysfunction is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
3
16
0
1
Order By: Relevance
“…Similarly, previous studies have shown that ANP and BNP are secreted in large amounts when cardiac hypertrophy occurs [1,31]. Increased myocardial fibrosis and collagen deposition are hallmarks of cardiac hypertrophy [13,32,33]. In the present study, histopathological examination of the heart tissue showed fibrosis in cardiac muscle along with the infiltration of acute and chronic inflammatory cells in the ISO group.…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 87%
“…Similarly, previous studies have shown that ANP and BNP are secreted in large amounts when cardiac hypertrophy occurs [1,31]. Increased myocardial fibrosis and collagen deposition are hallmarks of cardiac hypertrophy [13,32,33]. In the present study, histopathological examination of the heart tissue showed fibrosis in cardiac muscle along with the infiltration of acute and chronic inflammatory cells in the ISO group.…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 87%
“…widely used by the native population of the northeastern region to cure different metabolic disease, to explore its potential role in preventing HFHF-induced fatty liver in SD rats. Previously, we and others showed that chronic feeding of highfat high-fructose diet causes increase in body weight, insulin resistance, and hyperglycemia (Nizami et al, 2019). In the present study, we have observed a remarkable increase in body weight in the HFHF group indicating obesity in rats.…”
Section: Discussionsupporting
confidence: 73%
“…In an animal model of vitamin D deficiency, decreased protein kinase B/Akt phosphorylation and reduced expression of glucose transporter 4 (GLUT4) in cardiomyocytes was shown. This, in turn, resulted in insulin resistance by the myocardium, a significant downregulation of the endogenous antioxidant enzymes SOD2 and catalase, and diminished LVEF [41]. The high prevalence of vitamin D deficiency throughout the 12-month follow-up shown in our cohort of patients with HF may thus worsen or predispose them to alterations in glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%